Frequency of surgical procedures performed at the Recife Dental School clinic (Research, Society and Development, 2022)
This study shows the frequency of surgical procedures performed in the clinic of the Recife School of Dentistry. The institution offers surgical procedures to the population, interacting with the community and its social responsibility. The study aimed to present a theoretical overview on the theme "Right to Health and the Problem of Legal Demands for Medicines". In order to build a reflection and suggestions to reduce the bureaucracy of surgical procedures. In view of the social need for the use of the Unified Health System and the increase in demand by the population. The present study is descriptive, observational and cross-sectional where 500 randomly chosen charts were examined between the months of May to August 2018. The justification of the work is evidenced through the conception of survey of the quantitative carried out in the institution, discuss the topic with the social scope. Methods: for this, a literature review was conducted by searching for articles in PubMED/Medline, Lilacs and Scielo. The research instrument used was the interview for primary data collection and subsequent document analysis at the institution. It could be concluded that SUS is modern in its conception and endowed with an extensive social framework, however, it is insufficient to ensure what it precepts and in this scenario the Public Ministry has been an important instrument sought by civil society in order to ensure the right to health care.